2006
DOI: 10.1108/02635570610710809
|View full text |Cite
|
Sign up to set email alerts
|

The attribution of success and failure in IT projects

Abstract: Purpose -The purpose of this research is to determine how project managers attribute information technology (IT) project success and failure. Design/methodology/approach -IT personnel from large Australian organisations completed an adapted version of the Attributional Styles questionnaire, which asked them to attribute causes along a number of attribution dimensions, for IT projects which have either succeeded or failed. Findings -The results indicate that IT support workers attribute failure to external fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 40 publications
(43 reference statements)
3
82
1
5
Order By: Relevance
“…In Whittaker`s (1999) investigation, results showed that the top three factors of IS failure were: Slippage from the scope, change in the scope of technology, followed by costs overrun. According to Standing et al (2006), the top three reasons were lack of user support and involvement, lack of properly defined project scope and lack of executive management support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Whittaker`s (1999) investigation, results showed that the top three factors of IS failure were: Slippage from the scope, change in the scope of technology, followed by costs overrun. According to Standing et al (2006), the top three reasons were lack of user support and involvement, lack of properly defined project scope and lack of executive management support.…”
Section: Discussionmentioning
confidence: 99%
“…This paper studies the factors that may lead to the failure of projects in meeting the three aspects of Time, Cost and Quality. According to the literature, the common factors that lead to a project failure in meeting the success triangle are: (Process Driven Issues, Content Driven Issues, and Context Driven Issues) (Whittaker, 1999;K.T.Yeo, 2002;Kappleman et al, 2006;Standing et al, 2006;Kreps and Richardson, 2007;Tesch et al, 2007;Attarzadeh et al, 2008). These factors in brief are: 1) Process Driven Issues: Issues relating to business planning, project planning, project management and control, strategic formulation, and change management process.…”
Section: Factors That May Lead To the Failure Of Is Projectsmentioning
confidence: 99%
“…Observa-se, que a proposição 3 trata da necessidade da criação de mecanismos que identifiquem e deleguem as responsabilidades entre os membros da equipe de projetos, já que a identificação dessas responsabilidades exerce influência sobre o fracasso dos projetos de TI (Standing et al, 2006). Ainda, segundo os autores, determinada pelas diferentes percepções de cada um dos principais participantes do projeto, a auto-avaliação adquire importância devido ao seu potencial para justificar, corroborar ou eximir um eventual fracasso do projeto.…”
Section: Análise Das Informações Relacionadas Aos Mecanismos Que Idenunclassified
“…15 Effective monitoring and control Schmidt et al, 2001;Jones,1996;OGC,2005;Beynon-Davies, 1999;Humphrey, 2005;Mahaney and Lederer, 2003;Ewusi-Mensah, 1997;BCS, 2004;Reel, 1999;Oz and Sosik, 2000;Baccarini et al, 2004;Sauer and Cuthbertson, 2003;12 27.9 16 Adequate resources Kappelman et al, 2006;Standish Group, 1995Jiang and Klein, 2000;Baccarini et al, 2004;Ewusi-Mensah and Prazasnyski, 1994;Milis and Mercken, 2002;Oz and Sosik, 2000;Jones, 2006;Beynon-Davies, 1999;Leveson, 2004 11 25.6 17 Good leadership Schmidt et al, 2001;OGC,2005;Baccarini et al, 2004;Glaser, 2004;Humphrey, 2005;Drummond, 1998;Ewusi-Mensah, 1997;Standing et al, 2006;Reel, 1999;Clegg et al, 1997;Oz and Sosik, 2000;11 25.6 18 Risk management Whittaker, 1999;OGC, 2005;Yeo, 2002;Jiang et al, 1999;EwusiMensah, 1997;Leveson, 2004;Nuseibeh, 1997;Charette, 2005;BCS, 2004;…”
Section: Non-technical Factors Versus Technical Factorsmentioning
confidence: 99%
“…Res. Essays Schmidt et al, 2001;Sauer and Cuthbertson, 2003;Yeo, 2002;Jiang and Klein, 2000;Beynon-Davies, 1999;Glaser,2004;Humphrey, 2005;Drummond, 1998;Jiang et al, 2001;Charette, 2005;10 23.3 20 Effective change and configuration management Schmidt et al, 2001;Taylor, 2006;Kappelman et al, 2006;Jones,1995;Whittaker, 1999;Baccarini et al, 2004;BCS, 2004;Taylor, 2000;Oz and Sosik, 2000;Sauer and Cuthbertson, 2003 10 20.9 21 Supporting tools and good infrastructure Jones,1996Jones, , 1995Jiang et al, 1999;Ewusi-Mensah, 1997;Ewusi-Mensah and Prazasnyski, 1994;Leveson, 2004;Standish Group, 2006 22 Committed and motivated team Standish Group, 1995;Beynon-Davies, 1999;Jiang et al, 1999;Mahaney and Lederer, 2003;Ewusi-Mensah, 1997;Oz, 1994;Standing et al, 2006;Reel, 1999;Milis and Mercken, 2002 9 20.9 23 Good quality management Jones, 2006Jones, , 1996Jones, , 1995Baccarini et al, 2004;…”
Section: Non-technical Factors Versus Technical Factorsmentioning
confidence: 99%